2003
DOI: 10.1093/pcp/pcg121
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Cytoplasmic DNA in Male Reproductive Cells to Determine the Potential for Cytoplasmic Inheritance in 295 Angiosperm Species

Abstract: Mature pollen grains of 295 angiosperm species were screened by epifluorescence microscopy for a marker that denotes the mode of cytoplasmic inheritance. We used the DNA fluorochrome DAPI (4',6-diamidino-2-phenylindole) for pollen cell staining. The presence or absence of fluorescence of cytoplasmic DNA in the generative cell or sperm cells was examined in each species. The species examined represented 254 genera and 98 families, and 40 of these families had not been previously studied in this regard. The cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
162
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(172 citation statements)
references
References 18 publications
6
162
0
4
Order By: Relevance
“…Irrespective of the inheritance mode, however, we noticed that organelle DNAs are cytologically absent in pollen vegetative cells (Matsushima et al, 2008a;Sakamoto et al, 2008). A survey of numerous mature pollen grains using DAPI staining has revealed that almost all angiosperm species lack cytologically detectable organelle DNAs in pollen vegetative cells (Corriveau and Coleman, 1988;Mogensen, 1996;Zhang et al, 2003;Wang et al, 2010). It is noteworthy that pollen vegetative cells do not contribute to fertilization, but they do contain numerous plastids and mitochondria, which might be necessary for a pollen tube to germinate, elongate, and deliver sperm cells into the embryo sac.…”
Section: Introductionmentioning
confidence: 91%
“…Irrespective of the inheritance mode, however, we noticed that organelle DNAs are cytologically absent in pollen vegetative cells (Matsushima et al, 2008a;Sakamoto et al, 2008). A survey of numerous mature pollen grains using DAPI staining has revealed that almost all angiosperm species lack cytologically detectable organelle DNAs in pollen vegetative cells (Corriveau and Coleman, 1988;Mogensen, 1996;Zhang et al, 2003;Wang et al, 2010). It is noteworthy that pollen vegetative cells do not contribute to fertilization, but they do contain numerous plastids and mitochondria, which might be necessary for a pollen tube to germinate, elongate, and deliver sperm cells into the embryo sac.…”
Section: Introductionmentioning
confidence: 91%
“…However, there is an apparent bias in the proportion of their occurrence (Kuroiwa, 1991;Mogensen, 1996;Hagemann, 2004). In angiosperms, maternal inheritance dominates over the others: cytological studies (see below) suggest that approximately 80% of all species show maternal inheritance, and that the remaining species show biparental inheritance (Corriveau and Coleman, 1988;Zhang et al, 2003). In contrast, uniparental paternal inheritance of plastids is very rare, and is only reported in the kiwi plant (Actinidia deliciosa).…”
Section: Types Of Plastid Inheritance -Maternal Inheritance Is Commonmentioning
confidence: 99%
“…In contrast, such DAPI signals are not detected in maternal inheritance species (Miyamura et al, 1987). This disparity serves as a convenient method for assessing the 'potential' for biparental inheritance (Corriveau and Coleman, 1988;Zhang et al, 2003). In fact, it has enabled us to estimate that 80% of angiosperms exhibit maternal inheritance.…”
Section: Do Plastid Dnas Decrease During Pollen Development?mentioning
confidence: 99%
“…The trnK gene sequence determined in the present study which belongs to chloroplast DNA is mostly of maternal inheritance in angiosperm. 26) Our results suggested that at least C. officinale and L. chuanxiong were not from the same maternal line. Morphology, cytogenetic characters 9,10) and chemical constitutions [10][11][12] revealed the 2 species were quite different.…”
Section: Discussionmentioning
confidence: 62%